Treatment of periodontitis and C‐reactive protein: A systematic review and meta‐analysis of randomized clinical trials. (29th August 2022) - Luthra, Shailly; Orlandi, Marco; Hussain, Syed Basit; Leira, Yago; Botelho, João; Machado, Vanessa; Mendes, José João; Marletta, Debora; Harden, Simon; D'Aiuto, Francesco
Abstract: Background: Systemic inflammation is implicated in the onset and progression of several chronic diseases. Periodontitis is a potential trigger of systemic inflammation. Purpose: To comprehensively appraise all the evidence on the effects of the treatment of periodontitis on systemic inflammation assessed by serum C‐reactive protein (CRP) levels. Data Sources: Six electronic databases were searched up to 10 February 2022 to identify and select articles in English language only. Study Selection: Twenty‐six randomized controlled clinical trials reporting changes amongst 2579 participants about CRP levels at 6 months or more after treatment. Data Extraction: Two reviewers independently extracted data and rated the quality of studies. Meta‐analyses were performed using random and fixed effect models. Risk of Bias: Risk of bias (RoB 2.0 tool) and quality of evidence (GRADEpro GDT tool) analyses were completed. Data Synthesis: Treatment of periodontitis reduced CRP levels by 0.69 mg/L (95% confidence interval: −0.97 to −0.40) after 6 months, but limited evidence was retrieved from studies with longer follow‐ups. Similar findings were observed in participants with other co‐morbidities in addition to periodontitis. Greatest reductions were observed in participants with concentrations of CRP >3 mg/L at baseline. Limitations: High level of heterogeneity. Conclusions: Treatment of periodontitis reduces serum CRP levels (up to 6 months follow‐up) to a degree equivalent to that observed after traditional lifestyle or drug interventions. This evidence supports a causal association between periodontitis and systemic inflammation.